Distribution Patterns of Sea Horses Based on Sex Caught in the Waters of Morotai Island - Kismanto Koroy; Nurafni; Djainudin Alwi (East Asian Journal of Multidisciplinary Research, 2023)
This research aims to determine the distribution pattern of seahorses based on sex in the waters of Morotai Island, which are spread across the waters of Morotai Island. The research was carried out from June 2022 to July 2023 at 6 points spread across the waters of Morotai Island, including South Morotai, West South Morotai, East Morotai, Rao Island, North Morotai and Morotai Jaya. The results of the research showed that the number of individual seahorses found at the research location was 25 of three types, namely seven horse Hippocampus (3 males, four females), 17 Kellogi Hippocampus (7 males and 10 females) and one female Hippocampus spinosissimus. Meanwhile, analysis of the distribution pattern index for seahorses in the waters of Morotai Island shows a uniform distribution pattern.